Ex vivo immunosuppressive effects of mesenchymal stem cells on Crohn’s disease mucosal T cells are largely dependent on indoleamine 2,3-dioxygenase activity and cell-cell contact - Ciccocioppo, Rachele (Stem Cell Res Ther, 2015)
INTRODUCTION: Crohn’s disease (CD) is a disabling chronic enteropathy sustained by a harmful T-cell response toward antigens of the gut microbiota in genetically susceptible subjects. Growing evidence highlights the safety and possible efficacy of mesenchymal stem cells (MSCs) as a new therapeutic tool for this condition. Therefore, we aimed to investigate the effects of bone marrow-derived MSCs on pathogenic T cells with a view to clinical application. METHODS: T-cell lines from both inflamed and non-inflamed colonic mucosal specimens of CD patients and from healthy mucosa of control subjects were grown with the antigen muramyl-dipeptide in the absence or presence of donors’ MSCs. The MSC effects were evaluated in terms of T-cell viability, apoptotic rate, proliferative response, immunophenotype, and cytokine profile. The role of the indoleamine 2,3-dioxygenase (IDO) was established by adding a specific inhibitor, the 1-methyl-DL-tryptophan, and by using MSCs transfected with the small interfering RNA (siRNA) targeting IDO. The relevance of cell-cell contact was evaluated by applying transwell membranes. RESULTS: A significant reduction in both cell viability and proliferative response to muramyl-dipeptide, with simultaneous increase in the apoptotic rate, was found in T cells from both inflamed and non-inflamed CD mucosa when co-cultured with MSCs and was reverted by inhibiting IDO activity and expression. A reduction of the activated CD4(+)CD25(+) subset and increase of the CD3(+)CD69(+) population were also observed when T-cell lines from CD mucosa were co-cultured with MSCs. In parallel, an inhibitory effect was evident on the expression of the pro-inflammatory cytokines tumor necrosis factor-α, interferon-γ, interleukin-17A and -21, whereas that of the transforming growth factor-β and interleukin-6 were increased, and production of the tolerogenic molecule soluble HLA-G was high. These latter effects were almost completely eliminated by blocking the IDO, whose activity was upregulated in MSCs co-cultured with CD T cells. The use of a semipermeable membrane partially inhibited the MSC immunosuppressive effects. Finally, hardly any effects of MSCs were observed when T cells obtained from control subjects were used. CONCLUSION: MSCs exert potent immunomodulant effects on antigen-specific T cells in CD through a complex paracrine and cell-cell contact-mediated action, which may be exploited for widespread therapeutic use. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-015-0122-1) contains supplementary material, which is available to authorized users.